Carotid Angioplasty and Stenting versus Endarterectomy - Vinall, Maria (MD Conference Express, 2011)
This article discusses the Carotid Revascularization Endarterectomy versus Stenting Trial [CREST; NCT00004732], which was a prospective, multicenter, randomized, controlled trial that compared carotid endarterectomy and carotid angioplasty and stenting in participants with symptomatic and asymptomatic stenosis.